Vibration Mitigation in the Transport of Fruit Boxes Using 3D-Printed Devices - Pedro Sanchez-Cachinero; Cristina Aguilar-Porro; Rafael R. Sola-Guirado (Agriculture)
The transport of freshly post-harvested fruit to its collection point is mainly achieved using trailers over uneven terrain, which generates impacts and vibrations that negatively affect the quality of the fruit. Although some solutions to mitigate these effects have been proposed in previous studies, none of them are applied directly to the source of the problem, i.e., the transport boxes. In this context, metamaterial sheets inspired by the design of quasi-zero stiffness isolators (QZSs) open up the possibility of exploring ways of vibration isolation thanks to their associated nonlinear characteristics. In this work, ABS sheets with different internal geometries were manufactured and compared as possible bottoms of transport boxes. Vibration reduction not only protects the physical integrity of the fruit, avoiding visible damage such as bumps or bruises, but also preserves its chemical properties, such as texture and freshness, which directly impacts its shelf life and presentation for sale. The design variables analyzed for these geometries included the number of ribs, their thickness and their angle of inclination. In these specimens, their behavior to impact-type forces and their experimental dynamic behavior were studied using an electromagnetic shaker against a sinusoidal signal and against the uniaxial vibration recorded at the base of a trailer in a real rural route. The results showed that the specimens with a rib angle of 30° and a thickness of 0.4 mm showed the best impact performance and a higher amplification of vibration transmissibility in the steady state. In the presence of the signal recorded on the route, transmissibility reduction percentages between 13% and 19% were obtained in the principal acceleration impact.